“We won’t go to paradise for what we have done there…” The picture of the Soviet-Afghan War in the documentary fictional prose of Svetlana Alexievich, Boys in Zinc - Stępniak, Anna (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
The object of research discussed in this article is the documentary prose of Svetlana Alexievich. We are concerned with the powerful stream of documentary evidence in modern literature and the special nature of this genre. We drew attention to Boys in Zinc, a novel that offer a unique image of the truth about the Soviet-Afghan War, an expensive and pointless conflict. The book shows the harsh realities of the war (the ruthless army, the shame and shattered lives of the veterans), and the authorities, ruthless and cynical in sending young and unready young men to war.